Exosomes in Cardiovascular Diseases: Pathological Potential of Nano-Messenger - Jadli, Anshul S.; Parasor, Ananya; Gomes, Karina P.; Shandilya, Ruchita; Patel, Vaibhav B. (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular disease (CVD) represent a major global health problem, due to their continued high incidences and mortality. The last few decades have witnessed new advances in clinical research which led to increased survival and recovery in CVD patients. Nevertheless, elusive and multifactorial pathophysiological mechanisms of CVD development perplexed researchers in identifying efficacious therapeutic interventions. Search for novel and effective strategies for diagnosis, prevention, and intervention for CVD has shifted research focus on extracellular vesicles (EVs) in recent years. By Transporting molecular cargo from donor to recipient cells, EVs modulate gene expression and influence the phenotype of recipient cells, thus EVs prove to be an imperative component of intercellular signaling. Elucidation of the role of EVs in intercellular communications under physiological conditions implied the enormous potential of EVs in monitoring and treatment of CVD. The EVs secreted from the myriad of cells in the cardiovascular system such as cardiomyocytes, cardiac fibroblasts, cardiac progenitor cells, endothelial cells, inflammatory cells may facilitate the communication in physiological and pathological conditions. Understanding EVs-mediated cellular communication may delineate the mechanism of origin and progression of cardiovascular diseases. The current review summarizes exosome-mediated paracrine signaling leading to cardiovascular disease. The mechanistic role of exosomes in cardiovascular disease will provide novel avenues in designing diagnosis and therapeutic interventions.